Russia's Foreign Policy And The Search For A Role In The New International Order - Kanoua, Nizar; Katabi, Nour (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research attempts to discuss the issue of Russian foreign policy since the collapse of the Soviet Union to the present time, reviewing the elements of force and the threat facing Russia to achieve its strategic objectives, so we will discuss this subject through the main axes: First: the situation of Russia after the collapse of the Soviet Union, the second: challenges and elements possessed by Russia To achieve its objectives, and the third: Russian foreign policy towards the Syrian crisis in an attempt to learn the future of Russia and its status as a superpower in the international system in the presence of different forces. يحاول هذا البحث مناقشة مسألة السياسة الخارجية الروسية منذ انهيار الاتحاد السوفييتي وحتى الوقت الحاضر مستعرضاً عناصر القوة والتهديد التي تواجه روسيا لتحقيق أهدافها الإستراتيجية، لذلك سنبحث هذا الموضوع من خلال محاور رئيسية الأول: وضع روسيا بعد انهيار الاتحاد السوفييتي، الثاني: التحديات والمقومات التي تمتلكها روسيا لتحقيق أهدافها، والثالث: السياسة الخارجية الروسية تجاه الأزمة السورية في محاولة لمعرفة مستقبل روسيا ومكانتها كدولة عظمى في النظام الدولي في ظل وجود القوى المختلفة.